English English - Afwan Faizin; Khamami Zada (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This article examines the radical transformation of the Saudi Arabian legal system under Vision 2030, marking a fundamental shift from the supremacy of traditional judicial interpretation to the codification of state positive law. The analysis focuses on Crown Prince Mohammed bin Salman’s (MBS) epistemological maneuver to limit the authority of "Ahad Hadith" (single-narrator reports) in the public sphere, mandating that state law rely exclusively on the Qur'an and Mutawatir Hadith. Using a juridical-normative approach and critical discourse analysis, this study tests the consistency of this doctrine within recent legislative packages, specifically the Personal Status Law, the Civil Transactions Law, and Evidence Law. The study covers a methodological inconsistency that the state rejects Ahad Hadith in economic matters to ensure investment certainty but retains them in socio-familial issues to maintain patriarchal stability. Consequently, this article concludes that Saudi legal reform is not a pure theological purification but a "pragmatic legal hybridity" which epistemologically lacks a strong academic basis. The claim of relying solely on Mutawatir Hadith serves as a discursive strategy for the "nationalization of Sharia," effectively reducing the role of clerics and judges from autonomous interpreters of divine law to bureaucratic executors of state statutes, serving political stability and global economic interests.